Comparison of Livestock in Sudan and Indonesia Based on Research Trends Using the Semantic Scholar Database - Tasnin Hunin Abdelwhab Mohamed; Hasan Ishag Hassan Haren; Sari Tuswati; Doso Sarwanto (Faculty of Animal Husbandry, Wijayakusuma Purwokerto University, 2025)
This study presents a descriptive analysis of livestock research trends in Sudan and Indonesia using data extracted from the Semantic Scholar database. The objective was to compare research volume, thematic focus, and collaboration networks over the period 2003–2023 through bibliometric and text-mining approaches. We examined publication growth patterns, dominant topics, and institutional partnerships, based on the hypothesis that research activities differ due to distinct socio-economic and environmental conditions. After data cleaning and normalization of affiliations, 1,245 publications were identified for Sudan and 1,876 for Indonesia. Metadata such as publication year, authorship, citations, keywords, and institutions were analyzed. Indicators including annual output, citations per paper, and h-index values quantified productivity and influence. Network analysis revealed collaboration structures and leading institutions, while keyword co-occurrence and Latent Dirichlet Allocation (LDA) identified prevalent themes with coherence scores above 0.65. Results show that Indonesia exhibits higher productivity and global interconnectedness (network density = 0.35) than Sudan (0.21), alongside a greater citation impact (12.4 vs. 8.7 citations per document). Thematically, Sudan emphasizes pastoral systems, vector-borne disease control, and biodiversity, whereas Indonesia focuses on integrated farming, feed efficiency, and zoonoses. These findings highlight opportunities: enhancing international collaborations for Sudan and broadening thematic diversity in Indonesia to strengthen sustainable livestock research.